Personnel flux and workplace anxiety: Personal and interpersonal consequences of understaffing in UK ultrasound departments. Issue 1 (February 2019) - Miller, P.K.; Waring, L.; Bolton, G.C.; Sloane, C.
Abstract: Introduction: By 2013, the UK government's Migration Advisory Committee had determined sonography to be a formal shortage speciality, and understaffing remains a key concern for research in the domain. This paper, emergent of a qualitative study funded by Health Education North West, explores unit managers' perspectives on the present state of UK ultrasound. The focus herein falls upon the personal and interpersonal consequences of this circumstance for individuals working in specific understaffed departments. Methods: A thematic analysis informed by a Straussian model of Grounded Theory was utilised; N = 20 extended accounts provided by ultrasound department leads in public (n = 18) and private (n = 2) units were collected and analysed accordingly. Results: The global themes addressed herein describe (a) how both inter-departmental movement of senior sonographers and early retirement, within a nationally understaffed picture, impacts upon local knowledge economies, and (b) how such staffing instabilities can undermine the day-to-day confidence of managerial staff and practicing sonographers alike. Conclusions: It is personnel flux, rather than simple short-staffing, that is reported to cause the greatest social-psychological problems for both managers and sonographers. The issues raised herein require further examination from the perspective of sonographers themselves, in order to corroborate the views of the managers interviewed. Highlights: Many public ultrasound departments are understaffed, and in personnel flux. The costs of understaffing are not evenly distributed across departments. Early retirement exacts a heavy price upon the knowledge economy in ultrasound. Persistent migration of staff to 'greener pastures' disrupts managerial efficacy. Staffing flux undermines departmental morale more than simple understaffing.